2013
DOI: 10.4103/2225-4110.114904
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ethyl Acetate Fraction of Stereospermum Suaveolens Against Hepatic Oxidative Stress in STZ Diabetic Rats

Abstract: Stereospermum suaveolens is a folk remedy for the treatment of diabetes and liver disorders in southern parts of India. In the present study, the protective effect of the ethyl acetate fraction of ethanol extract from S. suaveolens against hepatic oxidative stress was evaluated in streptozotocin (STZ)-induced diabetic rats for 14 days. The ethyl acetate fraction was administered orally to the STZ diabetic rats at the doses of 200 and 400 mg/kg. Blood glucose level was measured according to glucose oxidase meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In our study, the level of TAS in rats treated with MTX, were significantly lower compared to healthy control group. Previous studies indicated decreased antioxidant capability and increased oxidative stresses provokes hepatic damage [ 42 , 56 , 73 ]. In groups V and VI (turmeric + MTX), serum TAS were elevated compared to group III (MTX treated animals), but statistically significant results were obtained when we used higher concentration of turmeric (200 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the level of TAS in rats treated with MTX, were significantly lower compared to healthy control group. Previous studies indicated decreased antioxidant capability and increased oxidative stresses provokes hepatic damage [ 42 , 56 , 73 ]. In groups V and VI (turmeric + MTX), serum TAS were elevated compared to group III (MTX treated animals), but statistically significant results were obtained when we used higher concentration of turmeric (200 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…ALT, AST, ALP and LDH). The increased levels of ALT, AST and ALP are conventional indicators of hepatocellular necrosis [28] . LDH is also an indicator of liver injury, although it has different isoenzymes and is not liver-specific [29] .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of herbal medications has developed to minimize hyperglycemia and other diabetes associated complications. In various investigations, the protective action of herbal antioxidants has been reported in scavenging free radicals and improving liver dysfunction in diabetic experimental models [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%